PEMODELAN TAPIS FABRY-PEROT PADA SERAT OPTIK DENGAN MENGGUNAKAN FIBER BRAGG GRATING - Septi Pramuliawati; Saktioto '; Defrianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Fabry-perot filter was successfully developed by a uniform Fiber Bragg Grating in fiber optic. A characterization of Bragg Grating was analyzed by using computational model with second-order of Transfer Matrix Method based on Coupled Mode Theory. The reflectivity, length of grating, and bandwidth were parametrics to determine the performance of single Bragg Grating. The transmission spectrum showed the longer grating is designed, the larger the reflectivity was produced, so that the transmission band was more narrow. The simulation carried out by varying the separation distance between two gratings was alsoevaluated by dual Bragg Grating. The separation distances from 0.5 cm to 9.5 cm with 1 cm length step. The simulation result showed the maximum peak value generated in the transmission spectrum increased directly proportional to the distance between the gratings. Thus, the grating can be applied as a filter. Only selected wavelength is allowed to transmit the signal until the end of the optical fiber.